1908
DOI: 10.1017/s0022172400015989
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicology of Nickel Carbonyl

Abstract: Nickel carbonyl poisoning is a particular instance of nickel poisoning.The lethal dose of nickel varies according to the method of application. When applied by subcutaneous injection, the physical condition of the compound influences the rate of absorption and therefore relatively large quantities may be required. In rabbits, the lethal dose is about 7½ mgrs. per kilogram body weight under the most favourable conditions when applied subcutaneously. In cats it is about 12½ mgrs. per kilogram body weight. When a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1938
1938
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The combination of these two reversible processes, with both an amino acid and a keto acid present, brings about the donation of the amino group from the amino acid to the keto acid. 14 '*»' tl6 '' +17 > 1 * 18…”
Section: Binding To Vitamin Bg and Transaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these two reversible processes, with both an amino acid and a keto acid present, brings about the donation of the amino group from the amino acid to the keto acid. 14 '*»' tl6 '' +17 > 1 * 18…”
Section: Binding To Vitamin Bg and Transaminationmentioning
confidence: 99%
“…Nickel carbonyl is a colorless, volatile liquid (boiling point, 43 C) that is particularly dangerous if inhaled. Armit 19 and Garland 153 demonstrated that the acute inhalation toxicity of nickel carbonyl is * Personal communication, Stafford, 1970.…”
mentioning
confidence: 99%
“…Armit (65) has studied the toxic doses of the carbonyls in some detail. The subject of most concern to the worker, however, is the quantity of the carbonyl which makes air dangerous to breathe.…”
Section: Thementioning
confidence: 99%
“…Acute inhalation causes severe pneumonitis and pulmonary edema,3-5 while longterm exposure to nickel carbonyl may result in increased incidence of carcinoma of the upper respiratory tracts and lungs. 2 ,5,6 The acute pathologic changes produced by nickel carbonyl were first described by Armit in 1907. 7 soning have appeared since then.…”
mentioning
confidence: 99%
“…2 ,5,6 The acute pathologic changes produced by nickel carbonyl were first described by Armit in 1907. 7 soning have appeared since then. 1,3,4,B Sunderman and his co-workers have been engaged in the study of hazards of nickel carbonyl exposure for the past 20 years and have studied the pathologic effects as well as investigated therapy of nickel poisoning in both laboratory animals and men.3-6,B-ll The purpose of this paper is to present a fatal case of nickel carbonyl poisoning and to discuss the current most effective method oftreatment.…”
mentioning
confidence: 99%